On composite sampling for monitoring generic and antibiotic-resistant coliforms in irrigation ponds - Stocker, Matthew Daniel; Smith, Jaclyn Elizabeth; Pachepsky, Yakov (Frontiers in Water, 2024)
The presence of fecal bacteria in irrigation waters is well documented in causing human and animal outbreaks, with the potential for antibiotic-resistant pathogens increasing the seriousness of these infections. Approaches to sampling fecal and antibiotic-resistant bacteria in irrigation waters used in raw food production require standardization to quantify and discern potential spatiotemporal trends in antibiotic-resistant bacteria (ARB). Composite sampling is widely used to reduce the cost and time of processing samples while estimating spatial or temporal variation in contaminant concentrations. The objectives of this work were to evaluate the spatial variation in generic and ARB in several irrigation ponds and assess the effectiveness of composite sampling in estimating the average of individual samples. In a grid-like fashion, five irrigation ponds were sampled for generic and antibiotic resistant E. coli and total coliforms using the Colilert Quanti-Tray/2000 with and without tetracycline and cefotaxime added. Individual samples were composited in sample sets including all samples, only bank samples, and only interior samples. Coefficients of variations in general were high (> 100 %) for generic bacteria and higher for ARB (140 -290 %). Concentrations of all measured bacteria were lower in the pond interior locations than the banks. The percentage of tetracycline resistant E. coli varied among ponds from averages of 0% to 23%. No cefotaximeresistant E. coli were detected in any of the ponds whereas the cefotaxime-resistant total coliforms were detected at each site. The average percentage of cefotaxime resistant total coliforms varied from 1.1 to 13.8 % among ponds. E. coli concentrations in composite samples did not significantly differ from either the mean or median of the individual sample sets in 89 % and 83 % of cases, respectively, indicating composite sampling to be effective in capturing spatial variation of both generic and ARB. Results of this work can be used to aid in the development of better strategies for surveilling antibiotic resistance in aquatic environments.